2015
DOI: 10.1186/s40463-015-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of nasal packing post rhinoplasty: Does it increase periorbital ecchymosis? A prospective study

Abstract: BackgroundPeriorbital edema and ecchymosis following rhinoplasty is disturbing for both the patients and their surgeons. The study aim was to determine whether nasal packing after lateral osteotomies in rhinoplasty surgery increases the risk of periorbital ecchymosis post-operatively.MethodsThis was a prospective self-controlled single-blinded study. Seventy four patients who underwent rhinoplasty with bilateral lateral osteotomies by a single surgeon were enrolled in the study. Nasal cavity packing for one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It involves several diverse approaches according to the specific deformities. [1][2][3][4] Rhinoplasty involving osteotomy of the nasal bones is one of the riskiest processes and results in a less controllable outcome. Osteotomy is generally performed in cases of correction of open roof deformity, reduction in the nasal pyramid, removal of convexity or unevenness, and straightening of the nasal bones.…”
Section: Introductionmentioning
confidence: 99%
“…It involves several diverse approaches according to the specific deformities. [1][2][3][4] Rhinoplasty involving osteotomy of the nasal bones is one of the riskiest processes and results in a less controllable outcome. Osteotomy is generally performed in cases of correction of open roof deformity, reduction in the nasal pyramid, removal of convexity or unevenness, and straightening of the nasal bones.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, clinical evidence suggests that nasal packing is ineffective and precipitates complications. Nasal packing compresses nasal capillaries, blocks venous return, and forces blood into the eyelid, leading to increased severity of periorbital edema and ecchymosis [32].…”
Section: Significance Of the Study Findingsmentioning
confidence: 99%
“…A significantly more severe and prolonged periorbital ecchymosis was found on the fourth and seventh postoperative day on the packed side. 51 The authors concluded that nasal packing should be avoided if possible.…”
Section: Tapingmentioning
confidence: 99%